Software implementation of LTE-advanced using Matlab Simulink - Mostafa, Wessam; Mohamed, Eman; Zekry, Abdelhalim (International Journal of Engineering and Technology, 2017)
Long Term Evolution Advanced (LTE-A) is the evolution of the LTE that developed by 3rd Generation Partnership Project (3GPP).LTE-A exceeded International Telecommunication Union (ITU) requirements for 4th Generation (4G) known as International Mobile Telecommunications (IMT-Advanced). It is formally introduced in October 2009. This paper presents a study and an implementation of the LTE-A downlink physical layer based on 3GPP release 10 standards using Matlab simulink. In addition, it provides the LTE-A performance in terms of Bit Error Rate (BER) against Signal to Noise Ratio (SNR) for different modulation and channel coding schemes. Moreover, different scenarios of Carrier Aggregation (CA) are modeled and implemented. The Simulink model developed for the LTE-A transceiver can be translated into digital signal processor DSP code or VHDL on FPGA code.